Management Strategy in a Large Accounting Firm: A Comment. - Brooks, Kenneth; Schroeder, Richard (The Accounting Review, 1979)
Abstract The participation observation method, though not extensively utilized in the field of accounting, is recognized as a credible technique for the development of understandings concerning complex social settings and relationships. The philosophical grounding for the approach is the assumption that a viable avenue for examining such an organizational setting is through immersion of the researcher into the milieu of the social interaction. The technique also requires a longitudinal view of the organization in as complete an array of situations as possible. Given the complexity of public accounting firms, it is questionable as to whether observations over a brief period are sufficient. This concern is compounded by the decision not to observe during the busiest part of the firm year. There has been precious little research on the nature and performance of public accounting firms, but the researcher who gains access to an organization and then fails to discuss findings in relation to existing research does a disservice.